Mediating piety: technology and religion in contemporary Asia - Lim, Francis Khek Gee (Social sciences in Asia, 2009)
Charismatic technology / Francis Khek Gee Lim -- Religion in the age of technology -- Technologies, religion and social mediation / Bryan S. Turner -- The fate of God in the age of technology / Anton Sevilla -- Technology, religion and nationalism -- A message from Ashabirin : high technology and political Islam in Indonesia / Sulfi kar Amir -- Powerpointing Islam : form and spiritual reform in Reformasi Indonesia / Daromir Rudnyckyj -- Mediating piety -- A spectacle of worship : technology, modernity and the rise of the Christian megachurch / Joseph Nathan Cruz -- The "short-waved faith" : Christian broadcasting and Protestant conversion of the Hmong in Vietnam / Ngo Thi Thanh Tam -- 'New media', religious discourse, community -- Shopping for God : media and religion in Singapore / Robin Chee and James Chen -- The new face of global evangelism : virtualizing spiritual experience / Jayeel Serrano Cornelio -- Religious ecology on the internet: a case study of Tibetan Buddhism / Low Yuen Wei